Поховальний обряд ранньосередньовічного Верхньо-Салтівського могильника: досвід статистичного аналізу - Аксьонов, В.С. (Археологія, 2018)
В роботі наводяться підсумки статистичної обробки мірних ознак поховальних споруд та деяких рис поховального обряду аланського населення, що залишило катакомбний могильник біля с. Верхній Салтів. Для узагальнення були залучені матеріали 226 катакомб з трьох ділянок Верхньо-Салтівського некрополя. The research of the Verkhniy Saltov burial ground, which have been conducted by Kharkiv archaeologists since 1984, allow expanding our knowledge ofthe Alancommunity sepulturalritesthatlefttheVerkhniySaltov—the Yutanov group ofnecropolises. For statistical processing the materials of 75 catacombs (197 burials) of BCM-I, 41 catacombs (70 burials) of BCM-III and 110 catacombs (245 burials) of BCM-IV were used. The carried-out statistical analysis showed a high extend of the majority of the measured signs standardization, characterizing the funeral constructions and a ceremony of the Alan population of Verkhniy Saltov. In general, the burial ceremony of the population, who left the Verkhniy Saltov burial ground, from our point of view, finds the greatest similarity to the funeral ceremony presented in the 7th and 8th groups of the Alanian catacomb burial grounds of the second half of the 5th — the first half of the 8th century CE, from the territory of the North-Eastern Caucasus. The average filling capacity of funeral chambers on different sites of the burial ground connects them with family collectives. The presence of burials with different orientation of the deceased in the chamber (the head to the left of the entrance, the head to the right of the entrance, feet to the entrance, the head to the entrance) on all the sites of the burial ground should be considered as an evidence of the multiethnic structure of the population of Verkhniy Saltov with one dominating group. Исследования Верхне-Салтовского могильника, проводимые харьковскими археологами с 1984 г. и по настоящее время, позволяют расширить наши знания относительно погребальной обрядности аланской общности, оставившей Верхне-Салтовскую — Ютановскую группу некрополей. Для статистической обработки были использованы материалы 75 катакомб (197 погребений) ВСМ-I; 41 катакомба (70 погребений) ВСМ-III и 110 катакомб (245 погребений) ВСМ-IV. Проведенный статистический анализ показал высокую степень стандартизации большинства мерных признаков, характеризующих погребальные сооружения и обряд аланского населения Верхнего Салтова. В целом погребальный обряд населения, оставившего Верхне-Салтовский могильник, как нам представляется, находит наибольшее сходство с погребальным обрядом, представленным в 7 та 8 группах аланских катакомбных могильников второй половины V — первой половины VIII вв. с территории Северо-Восточного Кавказа. Средняя наполняемость погребальных камер на разных участках могильника связывает их с семейными коллективами. Присутствие на всех участках могильника погребений с разной ориентировкой покойника в камере (головой влево от входа, головой вправо от входа, ногами ко входу, головой ко входу), возможно, следует рассматривать как свидетельство о полиэтничной структуре населения Верхнего Салтова с одной доминирующей группой.